The THE INFLUENCE OF PERSONAL BRANDING ON THE BRAND IMAGE OF SECONDATE BEAUTY - Indah Fajar Rosalina (Prodi S1 Ilmu Komunikasi, Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Jakarta, 2023)
This study examines the influence of the concept of Personal Branding on Brand Image Secondary Beauty. Secondate Beauty is a cosmetics company owned by Titan Tyra, a beauty influencer who is quite well-known among cosmetic fans in Indonesia. Secondate Beauty is here and has a place in the Indonesian cosmetic industry which is quite successful even though it is relatively young. Relying on the delivery of promotional materials from Titan Tyra made the brand, which was only three years old, sold out in just seven minutes at the launch of its first product, so this is the reason for researchers to find out how much influence Titan Tyra's personal branding has as an effort to increase Brand Image Secondate. Beauty. Given that personal branding today is one of the tools for success in promotion. Personal branding aims as a medium to direct other people's perceptions of individuals or products so as to create the impression of selling points of something, both in the field of products and services, so that this becomes one of the success factors in improving the company's product image. This study uses a quantitative causality method that seeks to find out the relationship and influence between variables X (personal branding) and variable Y (brand image), by distributing questionnaires to 100 respondents to Titan Tyra's Instagram followers, so that a correlation coefficient of 0.765 is obtained, which means it has a strong relationship. Meanwhile, the result of the simple linear regression test is 9.105 + 0.651 X, which means, if there is no Titan Tyra personal branding, then the Secondary Beauty brand image is 9.105 and if there is personal branding then the Secondary Beauty brand image will increase by +0.651. In addition, the results of the analysis of the coefficient of determination show a figure of 58.5%, which means that Variable X Personal Branding contributes 58.5% to Variable Y Brand Image